Induced pluripotent stem cells in companion animals: how can we move the field forward? - Barrachina, Laura; Arshaghi, Tarlan Eslami; O'Brien, Aisling; Ivanovska, Ana; Barry, Frank (Frontiers in Veterinary Science, 2023)
Following a One Medicine approach, the development of regenerative therapies for human patients leads to innovative treatments for animals, while pre-clinical studies on animals provide knowledge to advance human medicine. Among many different biological products under investigation, stem cells are among the most prominent. Mesenchymal stromal cells (MSCs) are extensively investigated, but they present challenges such as senescence and limited differentiation ability. Embryonic stem cells (ESCs) are pluripotent cells with a virtually unlimited capacity for self-renewal and differentiation, but the use of embryos carries ethical concerns. Induced pluripotent stem cells (iPSCs) can overcome all of these limitations, as they closely resemble ESCs but are derived from adult cells by reprogramming in the laboratory using pluripotency-associated transcription factors. iPSCs hold great potential for applications in therapy, disease modelling, drug screening, and even species preservation strategies. However, iPSC technology is less developed in veterinary species compared to human. This review attempts to address the specific challenges associated with generating and applying iPSCs from companion animals. Firstly, we discuss strategies for the preparation of iPSCs in veterinary species and secondly, we address the potential for different applications of iPSCs in companion animals. Our aim is to provide an overview on the state of the art of iPSCs in companion animals, focusing on equine, canine and feline species, as well as to identify which aspects need further optimization and, where possible, to provide guidance on future advancements. Following a ‘step-by-step’ approach, we cover the generation of iPSCs in companion animals from the selection of somatic cells and the reprogramming strategies, to the expansion and characterization of iPSCs. Subsequently, we revise the current applications of iPSCs in companion animals, identify the main hurdles and propose future paths to move the field forward. It is important to transfer the knowledge gained from human iPSCs to increase our understanding in the biology of pluripotent cells in animals, but it is also key to further investigate the differences among species to develop specific approaches for animal iPSCs that can significantly advance its application in veterinary medicine.